A selective detection approach for copper(ii) ions using a hydrazone-based colorimetric sensor: spectroscopic and DFT study. Issue 70 (30th November 2018) - Abdulazeez, Ismail; Basheer, Chanbasha; Al-Saadi, Abdulaziz A.
Abstract : The development of an efficient and miniaturized analytical approach to determine trace levels of toxic ions in aqueous fluids presents a current research challenge. Abstract : The development of an efficient and miniaturized analytical approach to determine trace levels of toxic ions in aqueous fluids presents a current research challenge. Hydrazone-based chemosensors are considered potential candidates due to their high sensitivity and selectivity towards heavy metal ions. Computational techniques can be properly implemented to elucidate possible modes of ligand–metal interaction and provide an in-depth understanding of the chemistry involved. The present study reports the use of 3-hydroxy-5-nitrobenzaldehyde-4-hydroxybenzoylhydrazone (3-HNHBH) ligand for highly sensitive, quick and re-usable colorimetric sensing of copper(ii ) ions in aqueous media. DFT calculations suggest that the complexation of 3-HNHBH with copper(ii ) ions adopts a seesaw coordination geometry and results in the largest HOMO–LUMO gap and most effective coulombic interaction compared to Zn and Ni counterparts. It demonstrated a high selectivity towards copper ions with a detection limit of 0.34 μg L −1 . The ligand was readily regenerated using a 0.5 M HCl solution, indicating its feasibility to be used as a re-usable sensor for the convenient detection of copper ions in aqueous media. The influence of metal interference, pH and solvents on the selectivity and regeneration of the ligand was also investigated.